PENGARUH KUALITAS LAYANAN KAMAR OPERASI TERHADAP KEPUASAN PASIEN DI RS X TEGAL - Srirahayu Rubiyanto; Sri Purwanti (MOTORIK Jurnal Ilmu Kesehatan, 2026)
Service quality will have an impact on satisfaction which can be interpreted as an emotional response felt by someone after comparing the expectations and performance of the product or service received. The study was conducted at X Tegal Hospital with the aim of determining the quality of operating room services on patient satisfaction as seen from the application of the Surgical Safety Checklist. This type of research is cross-sectional with a data collection method by direct interviews with 92 operating room patients at X Tegal Hospital by accidental sampling analyzed by linear regression using SPSS. Based on the results of the study, a Pearson correlation value of 0.848 was obtained. The regression results showed that service quality had a significant effect on patient satisfaction (p <0.0001) with a regression coefficient of 0.790 and an R square value of 0.719. This means that 71.9% of the variation in patient satisfaction can be explained by the quality of operating room services. Conclusion: good service quality can significantly increase patient satisfaction